Cantigi (Vaccinium varingifolium (Blume) Miq.) Di Jalur Pendakian Gunung Lawu Kabupaten Karanganyar Jawa Tengah - Efri Roziaty; Adnan Nurrahman Al Farisi (Bioeksperimen: Jurnal Penelitian Biologi, 2022)
Cantigi is one of the shrubs that grows at the height of the mountain. Camtigi is a plant endemic to the mountains. Among climbers, Cantigi is one of the fruits on the mountain that can be consumed. This study aims to determine the diversity of the Cantigi plant population that grows in the Mount Lawu area, Karanganyar Regency, Central Java. The research method is exploratory through exploration. The sampling technique was purpossive sampling. The selection of sampling locations was divided into 3 stations taken based on different altitudes. At an altitude of 2.819 – 3.025 m above sea level (Station I), an altitude of 3.025 – 3.192 (Station II) and an altitude of 3.192 – 3.265 (Station III). These three stations are the Mount Lawu Peak Area. The results of the study found that only 1 species of Cantigi was found in the top area of Mount Lawu, namely the species Vaccinium varingiaefolium Miq. The number of individuals encountered at each station were 67 individuals at an altitude of 2,819 – 3,025 m asl (Station I), 160 individuals at an altitude of 3.025 – 3.192 m asl (Station II) and 154 individuals at an altitude of 3.192 – 3.265 m asl (Station III). The highest number found was in the altitude range of 3.025 – 3.192 m above sea level. The results of the Diversity Index (H') obtained are 3,084 categorized as moderate and tend to be low. The conclusion of this study is that Cantigi is mostly found in areas with an altitude range of 3.025 – 3.192 m above sea level, which is about 160 individuals.